Primary Biliary Mucosa-associated Lymphoid Tissue Lymphoma Mimicking Hilar Cholangiocarcinoma - Seungha Hwang; Tae Jun Song; Seol So; Min Kyung Jeon; Eun Hye Oh; Byoung Soo Kwon; Sujong An; Myung-Hwan Kim (The Korean Journal of Gastroenterology, 2016)
Primary biliary mucosa-associated lymphoid tissue (MALT) lymphoma is extremely rare. We report a case of primary biliary MALT lymphoma with obstructive jaundice diagnosed by endoscopic biopsy, without surgical intervention. Obstructive jaundice was relieved by endoscopic drainage and endoscopic biopsy was done simultaneously during endoscopic retrograde cholangiopancreatography. Unnecessary surgical intervention can be avoided after pathological confirmation of lymphoma. The patient received radiotherapy, and is alive without any evidence of recurrence or biliary obstruction. Diagnosis of primary biliary lymphoma is very difficult because of its low prevalence. However, it should always be considered as a differential diagnosis, since when an accurate diagnosis is made, unnecessary surgical intervention can be avoided. (Korean J Gastroenterol 2016;68:114-118)